Checklist and a new species of Lippia (Verbenaceae) from the Diamantina Plateau, Minas Gerais, Brazil - Cardoso, Pedro Henrique; Menini Neto, Luiz; Trovó, Marcelo; Salimena, Fátima Regina Gonçalves (European Journal of Taxonomy, 2021)
The Diamantina Plateau is located in the central region of the Espinhaço Range, in the State of Minas Gerais, which is dominated by campo rupestre formations. We describe a new species of Lippia L., endemic to the Diamantina Plateau, and provide an annotated checklist and identification key for the 17 species of the genus occurring in the area. Lippia raoniana P.H.Cardoso & Salimena sp. nov. is mainly distinguished by its ovate leaves with adaxial and abaxial surfaces densely covered by sessile glandular trichomes, and drupaceous fruits with two pyrenes. It is known only from two populations, and thus can be provisionally considered as Critically Endangered. Details on the species’ ecology, as well as a comparison with morphologically similar species, a distribution map, and field photographs, are provided. In this work, we also present pictures of the 17 species in their habitats, and we hope that these illustrations will help in the identification and conservation of these taxa.